PENGEMBANGAN BUKU PANDUAN KESELAMATAN DAN KESEHATAN KERJA DI BENGKEL OTOMOTIF SMK NEGERI 2 PANGKALPINANG - Aditya Anugerah; Tafakur (Journal of Automotive Technology and Education, 2024)
Occupational safety and health is a culture that needs to be implemented in vocational learning. But until now, some vocational learning still ignores the importance of OSH culture. Therefore, vocational schools must always strive for an innovation to always implement an OSH culture, one of which is through the development of an OSH guidebook in implementing an OSH culture. Therefore, this research aims to: (1) Develop an OHS guidebook in the automotive workshop of SMK Negeri 2 Pangkalpinang as a practical guide in the automotive workshop; (2) Know the feasibility of the OHS guidebook in the automotive workshop of SMK Negeri 2 Pangkalpinang; (3) Know user responses regarding the OHS guidebook in the automotive workshop of SMK Negeri 2 Pangkalpinang. This research uses the development of the 4-D model. including: Define, Design, Develop, and Disseminate. This research was conducted at SMK Negeri 2 Pangkalpinang with a research subject of 30 students of class XI TKRO as a response to the K3 guidebook. Data collection used a questionnaire instrument with a Likert scale. The questionnaire instrument was tested for validity using expert judgment. The reliability of the instrument was tested using Cronbach alpha and then analyzed by quantitative descriptive analysis. The results of the study were: (1) The K3 guidebook in the Automotive Workshop for TKRO competency students of SMK Negeri 2 Pangkalpinang was developed with the 4-D development model, (2) The results of the guidebook assessment by material experts and media experts obtained the category "Very Feasible", (3) The results of responses by users obtained the category "Very Positive".